Pilot Trial of a Parenting and Self-Care Intervention for HIV-Positive Mothers: The IMAGE Program - Murphy, Debra A. (AIDS Care, 2016)
A pilot study was conducted to assess the effects of the IMAGE pilot intervention (Improving Mothers’ parenting Abilities, Growth, and Effectiveness) on mothers living with HIV (MLH). Based on Fisher and Fisher's IMB model (1992), the intervention focused on self-care and parenting behavior skills of MLH that affect maternal, child, and family outcomes. A randomized pretest-posttest two-group design with repeated assessments was used. MLH (n = 62) and their children ages 6 - 14 (n = 62; total N = 124) were recruited for the trial and randomized to the theory-based skills training condition or a standard care control condition. Assessments were conducted at baseline with follow-ups at 3, 6, and 12 months. Maternal, child, and family outcomes were assessed. Results show significant effects of the intervention for improving parenting practices for mothers. The intervention also improved family outcomes, and showed improvements in the parent-child relationship. IMAGE had a positive impact on parenting behaviors, and on maternal, child, and family outcomes. Given MLH can be challenged by their illness and also live in under-resourced environments, IMAGE may be viewed as a viable way to improve quality of life and family outcomes.